Reducing a cocrystal to nanoscale dimensions enables retention of physical crystal integrity upon dehydration. Issue 27 (23rd June 2017) - Peterson, Katherine E.; Henry, Rodger F.; Zhang, Geoff G. Z.; MacGillivray, Leonard R.
Abstract : We report the preparation and dehydration of a cocrystal of caffeine and 2, 4-dihydroxybenzoic acid. Abstract : We report the preparation and dehydration of a cocrystal of caffeine and 2, 4-dihydroxybenzoic acid. The dehydration of cocrystals of macro-dimensions results in destruction of crystal morphology; however, crystal morphology is retained when the cocrystal is reduced to nanometer-dimensions, despite a lack of pores to accommodate loss of water.